2000
DOI: 10.1046/j.1439-0388.2000.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and inheritance of canine elbow dysplasia in German Rottweiler

Abstract: A total of 2114 scores of elbow arthrosis from the official screening programme of the German Rottweiler Breeding Association (ADRK) were analysed in respect of prevalence and genetic disposition. 45.8% showed no signs of arthritis, 40.6% were scored in Grade 1 with minor osteophytes and 13.6% were affected by arthritis of clinical relevance (Grade 2 and 3). REML estimates showed a heritability of 28% and a litter variance of 6.4%. The only significant environmental fixed effect was gender. 39.1% of the male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
4
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 8 publications
3
23
4
13
Order By: Relevance
“…The estimated heritability for the ED score in the present study, according to IEWG guidelines, was lower than all estimates reported for other breeds (Beuing et al 2000;Janutta and Distl 2008). These heritability differences may be due to breed differences or to the method used for estimation (Janutta and Distl 2008).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The estimated heritability for the ED score in the present study, according to IEWG guidelines, was lower than all estimates reported for other breeds (Beuing et al 2000;Janutta and Distl 2008). These heritability differences may be due to breed differences or to the method used for estimation (Janutta and Distl 2008).…”
Section: Discussioncontrasting
confidence: 88%
“…Active genetic control based on diagnostic tests for con-dition and selective breeding are the best tools to prevent their occurrence . Radiographic examination of the elbow joints is currently the only widely used method for screening dogs for ED (Beuing et al 2000;Lewis et al 2011;Lavrijsen et al 2012). However, radiography has some limitations in the diagnosis of some primary ED lesions.…”
mentioning
confidence: 99%
“…Porém houve boa/moderada concordância para mensuração da incongruência radioulnar no plano sagital entre os observadores. Concluiu-se que nenhuma das cinco incidências radiográficas foi superior à outras para análise radiográfica, uma vez que cada projeção apresentou melhor identificação de um compartimento do cotovelo; medidas ao exame tomográfico para incongruência radioulnar não apresentam reprodutibilidade no corte dorsal, no corte sagital apresentaram boa e moderada concordância entre os observadores e que a mensuração do ângulo da incisura Figura 5.7-Imagens tomográficas reformatadas para mensuração da incongruência radioulnar nos planos sagital e dorsal,segundo o plano transversal, baseado nos estudos de Kramer et al (2006 FOURIE, 1998;GEMMILL et al, 2005), é um termo genérico para descrever má formação ou disfunção da articulação do cotovelo (LJUNGGREN et al, 1966;BEUING et al, 2000). É considerada um grupo de desordens do desenvolvimento que afeta cães de raças grandes (BEUING et al, 2000;MALM et al, 2008;MOORES et al, 2008;LAPPALAINEN et al, 2013) e gigantes (MOORES et al, 2008;MICHELSEN, 2012) e é a causa mais comum de claudicação de membros torácicos em cães jovens (FOX et al, 1982;KRAMER et al, 2006;BURTON et al, 2011;LAPPALAINEN et al, 2013).…”
Section: Agradecimentounclassified
“…A displasia do cotovelo cursa com manifestações clínicas e radiográficas de osteoartrose (OA), e a ela são relacionadas a não união do processo ancôneo (NUPA), fragmentação do processo coronóide medial (FPCM), osteocondrose do côndilo umeral (OC) e incongruência articular (IA) FOURIE, 1998;WALKER, 1998;BEUING et al, 2000;REICHLE et al, 2000;HAUDIQUET et al, 2002;MASON et al, 2004;GEMMILL et al, 2005;KEALLY;MCALLISTER, 2005;SAMOY et al, 2006;KRAMER et al, 2006;POLLARD, 2007;GEMMILL et al, 2007;MOORES et al, 2008;COOK;COOK, 2009;HOULTON, 2009;TEMWICHITR et al, 2010;GASCH et al, 2012;LAVRIJSEN et al, 2012).…”
Section: Agradecimentounclassified
See 1 more Smart Citation